The Moderating Role of Internship Experience between Campus Climate and Career Adaptability among Final-Year Students - Elza Ashifa Putri Zacky; Talitha Lintang Pertiwi (Universitas Islam Tribakti Lirboyo Kediri, 2026)
Career adaptability has become an essential resource for final-year students as they prepare to enter an increasingly complex labor market. This study examined the influence of campus climate on career adaptability and investigated whether internship experience strengthens this relationship. The study involved 153 final-year students selected through purposive sampling. Data were collected using the Indonesian version of the Career Adapt-Abilities Scale (CAAS) adapted by Sulistiani et al. (2018), the Campus Climate Scale adapted from Qotrunnada (2022) based on Fisher et al. (2020), and researcher-developed indicators of internship experience based on internship participation and duration. The data were analyzed using Moderated Regression Analysis (MRA). The results demonstrated that campus climate positively and significantly predicted career adaptability (B = 1.368; β = 0.703; p < 0.05), explaining 49.4% of the variance (R² = 0.494). However, the interaction between campus climate and internship experience was not statistically significant (p > 0.05), indicating that internship experience did not moderate the relationship. Furthermore, One-Way ANOVA revealed no significant differences in career adaptability across internship duration groups (F = 0.641; p > 0.05). These findings suggest that a supportive campus climate contributes substantially to students' career adaptability, whereas internship experience, as measured by duration, does not. Therefore, fostering a positive campus environment may be an important strategy for supporting students' preparation for future careers.